Integrasi Nilai Tri Hita Karana dalam Pelestarian Tradisi 'Belanjakan' sebagai Identitas Budaya Lokal di Kecamatan Masbagik Kabupaten Lombok Timur - Jamaludin; Rusdiana Yusuf; Adi Suriatno (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
The preservation of local culture is a crucial element in maintaining a community's identity, reflecting its values, history, and wisdom passed down through generations. This study aims to explore the role of the Tri Hita Karana philosophy in preserving the